Sex differences in pathogenesis and treatment of dyslipidemia in patients with type 2 diabetes and steatotic liver disease - Ábel, Tatjana; Benczúr, Béla; Csobod, Éva Csajbókné (Frontiers in Medicine, 2024)
Previously published studies have shown that women with type 2 diabetes have a higher risk of atherosclerotic cardiovascular disease than men with type 2 diabetes. The exact reason for this is not yet known. The association between metabolic dysfunction-associated steatotic liver disease and type 2 diabetes appears to be bidirectional, meaning that the onset of one may increase the risk of the onset and progression of the other. Dyslipidemia is common in both diseases. Our aim was therefore to investigate whether there is a sex difference in the pathogenesis and management of dyslipidemia in patients with type 2 diabetes and steatotic liver disease with metabolic dysfunction. While the majority of published studies to date have found no difference between men and women in statin treatment, some studies have shown reduced effectiveness in women compared to men. Statin treatment is under-prescribed for both type 2 diabetics and patients with dysfunction-associated steatotic liver disease. No sex differences were found for ezetimibe treatment. However, to the best of our knowledge, no such study was found for fibrate treatment. Conflicting results on the efficacy of newer cholesterol-lowering PCSK9 inhibitors have been reported in women and men. Results from two real-world studies suggest that up-titration of statin dose improves the efficacy of PCSK9 inhibitors in women. Bempedoic acid treatment has been shown to be effective and safe in patients with type 2 diabetes and more effective in lipid lowering in women compared to men, based on phase 3 results published to date. Further research is needed to clarify whether the sex difference in dyslipidemia management shown in some studies plays a role in the risk of ASCVD in patients with type 2 diabetes and steatotic liver disease with metabolic dysfunction.